PEMURNIAN, IDENTIFIKASI DAN UJI AKTIVITAS ANTIDIABETES SENYAWA METABOLIT SEKUNDER EKSTRAK ETIL ASETAT DAUN KACA PIRING (Gardenia augusta, Merr) - Chasani Mochamad; Hartiwi Diastuti; Rizka Aprilia (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2011)
Gardenia augusta, Merr is one of the family Rubiaceae species used as traditional medicine because it has medicinal properties, such as drug diabetes mellitus. These research have been done on this plant, among others, is the ability of the extract and the active fraction ethyl acetate extract of Gardenia augusta, Merr leaves to lowering blood sugar levels of rats. The purpose of this research was to purification of the active fraction of the ethyl acetate extract and identify the secondary metabolites of Gardenia augusta, Merr leaves as well as test that can be used antidiabetic. Purification was done by column chromatography which was eluted with n-hexane: ethyl acetate (7:1) and obtained four groups of fractions. The fractions of the TLC to obtain pure isolates F2 fraction with melting point 158-160 ° C. The antidiabetic activity of the isolate F2 fractions were tested into white rats by glucose tolerance methods. Isolate F2 fraction was identified by using UV and IR spectrophotometer. The results showed that isolate F2 fraction of ethyl acetate extract of Gardenia augusta, Merr leaves has a hypoglycemic effect of 21.05%. The secondary metabolites test showed a positive result for steroids. Analysis using UV spectrophotometer showed the electronic transition n → л * and transition л → л *. Analysis using IR spectrophotometric showed functional groups OH, C = O, CO, aliphatic C-H, C = C, C-C, CH3 symmetric and C-H outside the field. Key word: Gardenia augusta, Merr, diabetes mellitus, steroids